Calogênese, quantificação de rutina, atividade antioxidante de acessos de mangabeira e viabilidade polínica de coqueiro anão verde de Fiji - Machado, Caroline de Araújo (2018)
Mangaba (Hancornia speciosa Gomes) is a fruit species of tropical climate and native to Brazil. The objective of this work was to determine the antioxidant activity, the rutin content, and induction of callus in vitro in six mangaba accessions from Embrapa Coastal Tablelands Active Germplasm Bank. The experiments were conducted in the Laboratory of Plant Tissue Culture (Embrapa Coastal Tablelands) and Laboratory of Plant Anatomy (Federal University of Lavras). In vitro germinated seedlings were used as explants source (nodal, foliar, and internodal segments). The segments were inoculated for callus induction in MS culture medium containing different combinations of growth regulators. For the antioxidant activity of the in vivo accessions of leaf extracts, Barra do Itariri and Costa Azul obtained a greater free radical capture capacity (EC50 = 110.09 and 176.03g of dry extract/g of DPPH •) when compared with the other in vivo and in vitro accessions. Rutin was not detected in extracts from in vitro mangaba callus. The accessions Barra Itariri and Caju obtained the highest rutin concentrations (64.26 and 67.26 mg/L, respectively) in in vivo leaf extracts. The anatomical and morphological analysis of callus formed from leaf segment revealed sac cells (small agglomerated cells), aec cells (elongated agglomerated cells), sc cells (small cells), and rac cells (round agglomerated cells). Conversely, callus formed from the internodal segment revealed the initial formation of dedifferentiated cells, and allowed detecting the other organs present in the caulinary area. Due to the proliferation of lethal yellowing disease in coconut (Cocos nucifera L.), several studies have been carried out regarding the genetic improvement of the species, aiming at more tolerant materials, such as the Fiji green dwarf coconut. In this sense, the objective of this article was to evaluate the Fiji green dwarf coconut pollen viability by in vitro germination in different nutritional and abiotic conditions. A closed inflorescence was collected at the Tropical Research and Education Center, Homestead, Florida. For the pollen viability test, germination was evaluated at different temperature conditions (22, 25, 28, 30°C), in an incubator with light, with different Lora medium concentrations, supplemented with sucrose (40, 80, 120, and 160 g/L, respectively). The highest of germination percentage (44%) was achieved under Lora medium concentration of 4X supplemented with 160g/L of sucrose, at a temperature of 26.5ºC. The highest percentage of germination was achieved at 24 hours after inoculation.